Komunikasi Pembelajaran - Masdul, Muhammad Rizal (IQRA JURNAL ILMU KEPENDIDIKAN & KEISLAMAN, 2018)
The learning communication is a process of delivering a concept or an idea from someone to others in order to achieve the message effectively and efficiently in learning. There are 4 functions as stated by William I. Gordon: (1) Function of social communication, (2) expressive communication, (3) ritual communication and (4) function of instrumental communication. The principle of communication consists of respect, emphaty, audible, clarity, and humble. The effective communication in learning incredibly have the impact towards the achievement goal.